2020
DOI: 10.1136/bmjstel-2019-000549
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the construct validity of a haptic virtual caries simulation for dental education

Abstract: IntroductionTeaching dental caries removal is limited by the material and methods available in the preclinical teaching space. Plastic teeth do not simulate the tactile feel of a lesion and natural teeth do not allow for standardised training and assessment. A novel method for simulating caries has been reported. Here, to investigate the construct validity of a caries simulation, whether haptic simulation could contribute to the understanding of caries removal, the performance of first-year dental students on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…The detailed characteristics of the included studies are shown in Table 1 . HT was the most used in 18 of the selected studies, 12 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 VR simulator in three studies 39 40 41 and AR, 13 and interactive video games, 42 one study each. Access to all these technologies was through academic laboratories except in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed characteristics of the included studies are shown in Table 1 . HT was the most used in 18 of the selected studies, 12 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 VR simulator in three studies 39 40 41 and AR, 13 and interactive video games, 42 one study each. Access to all these technologies was through academic laboratories except in one study.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies assessed VR on theoretical knowledge. 13,37,40,42 Results showed significant difference in 14 of the selected studies in manual clinical skills 12,13,23,27,[29][30][31][34][35][36][38][39][40][41] and two studies in theoretical knowledge. 37,40…”
Section: Description Of the Study Characteristics Restorative Dentistrymentioning
confidence: 99%
“…Some researchers focused on exploring task-specific haptic training, including endodontic access opening, 30 caries detection and removal, [31][32][33] patient-centered training, 34 and the use of a "playback" mode (i.e., recording procedures performed by experts that can be played back by stu-dents for training purposes). 35,36 Although the initial shortterm evaluation was successful, the long-term impact as well as the task specific details that lead to effective learning are yet to be determined.…”
Section: Task-specific Haptic Trainingmentioning
confidence: 99%
“…Osnes et al (25) 2020 Investigar la validez de constructo de un ejercicio de simulación del tratamiento de caries dental mediante realidad virtual y háptica como herramienta de aprendizaje en estudiantes de odontología preclínica.…”
Section: Simuladores Tipo Fantomaunclassified
“…En otro estudio realizado en Reino Unido en el 2020 por Osnes et al25 se compara el desempeño de 112 estudiantes de odontología de primer año con 17 odontólogos. Con el propósito de determinar la validez del constructo de simulación del tratamiento de caries dental mediante realidad virtual y háptica, para ello se realizó un ejercicio que consistía en la eliminación de caries, ubicada a lo largo de la unión amelodentinaria en un tiempo de 15 minutos.…”
unclassified